Three-Dimensional Superhydrophobic Hollow Hemispherical MXene for Efficient Water-in-Oil Emulsions Separation - Haoran Chen; Riyuan Wang; Weiming Meng; Fanglin Chen; Tao Li; Dingding Wang; Chunxiang Wei; Hongdian Lu; Wei Yang (Nanomaterials, 2021)
A superhydrophobic macroporous material composed of hollow hemispherical MXene (HSMX) was synthesized by the thermal annealing of MXene-wrapped cationic polystyrene spheres (CPS@MXene). Notably, the spherical MXene shells exhibited highly efficient catalysis of the carbonization of CPS into carbon nanoparticles. Their insertion into the interlayer of MXene increased the d-spacing and created hollow hemispheres. The as-prepared HSMX with nanoscale walls had a lower packing density than MXene, but higher porosity, total pore volume, and total pore area. Moreover, the stacking of hollow hemispheres promoted the formation of a highly undulating macroporous surface and significantly improved the surface roughness of the HSMX-based 3D membrane, resulting in superhydrophobicity with a water contact angle of 156.4° and a rolling angle of 6°. As a result, the membrane exhibited good separation efficiency and Flux for emulsifier-stabilized water-in-paraffin liquid emulsions, which was dependent on its superhydrophobic performance and strong demulsification ability derived from the razor effect originating from the ultrathin walls of HSMX. This work provides a facile approach for the transformation of highly hydrophilic 2D MXene into superhydrophobic 3D HSMX, and opens a new pathway for the development of advanced MXene-based materials for environmental remediation applications.